2007
DOI: 10.1002/glia.20471
|View full text |Cite
|
Sign up to set email alerts
|

Dual regulation of astrocyte gap junction hemichannels by growth factors and a pro‐inflammatory cytokine via the mitogen‐activated protein kinase cascade

Abstract: Evidence that glutamate and ATP release from astrocytes can occur via gap junction hemichannels (GJHCs) is accumulating. However, the GJHC is still only one possible release mechanism and has not been detected in some studies, although this may be because the levels were below those detectable by the system used. Because of these conflicting results, we hypothesized that release from astrocyte GJHCs might depend on different astrocyte states, and screened for factors affecting astrocyte GJHC activity by measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 43 publications
1
25
0
1
Order By: Relevance
“…Finally, patch-clamp record- ings performed in astrocytes demonstrate that treatment with CM* generates singlechannel activity characterized by a unitary conductance (ϳ220 pS) already reported for Cx43 hemichannels (Contreras et al, 2003) and clearly different from Px hemichannels that are between 475 and 550 pS (Bao et al, 2004). Moreover, these findings make a link between recent reports showing that gap junction channels and hemichannels are oppositely regulated in cell lines transfected with Cx43 (De Vuyst et al, 2007) and that proinflammatory cytokines affect the activity of Cx hemichannels in astrocytes (Morita et al, 2007).…”
Section: Opposite Regulation Of Two Cx43 Functions In Astrocytessupporting
confidence: 75%
See 1 more Smart Citation
“…Finally, patch-clamp record- ings performed in astrocytes demonstrate that treatment with CM* generates singlechannel activity characterized by a unitary conductance (ϳ220 pS) already reported for Cx43 hemichannels (Contreras et al, 2003) and clearly different from Px hemichannels that are between 475 and 550 pS (Bao et al, 2004). Moreover, these findings make a link between recent reports showing that gap junction channels and hemichannels are oppositely regulated in cell lines transfected with Cx43 (De Vuyst et al, 2007) and that proinflammatory cytokines affect the activity of Cx hemichannels in astrocytes (Morita et al, 2007).…”
Section: Opposite Regulation Of Two Cx43 Functions In Astrocytessupporting
confidence: 75%
“…Recently, gap junction channels and hemichannels constituted by Cx43 were reported to be differentially regulated in C6 glioma cell lines (De Vuyst et at., 2007) and Cx43 hemichannels were shown to be sensitive to proinflammatory treatments in astrocytes (Morita et al, 2007). In addition, 24 h treatment with either conditioned medium harvested from LPS-activated MG (CM*)…”
Section: Conditioned Medium From Lps-activated Mg or Proinflammatory mentioning
confidence: 99%
“…Stage V-VI oocytes were defolliculated and isolated as described previously (45) followed by incubation in Kulori medium containing (in mM) 90 (46)) were subcloned into the expression vector pXOOM optimized for oocyte expression by addition of untranslated RNA-stabilizing elements (47). The coding sequence of the cDNA was verified by sequencing prior to linearization downstream from the poly(A) segments.…”
Section: Methodsmentioning
confidence: 99%
“…In rat astrocytes, we detected a DCFS-induced increase in uptake of ethidium and Yo-Pro which was, however, insensitive to Gd 3ϩ and therefore unlikely to be Cx43-mediated. A few research groups have previously reported DCFS-induced Lucifer Yellow uptake in astrocytic cultures (29,89), whereas other groups failed to detect DCFS-induced permeability to ethidium or calcein when astrocytes were grown in conventional medium (53,90). With the lack of a specific Cx43 inhibitor, we took advantage of the conditional Cx43 knock-out mice but detected no significant difference between the DCFS-induced uptake of ethidium or Yo-Pro in a comprehensive series of parallel experiments on astrocytes obtained from these animals in comparison with those obtained from WT mice.…”
Section: Figure 8 Dye Permeability Of Wild-type (Wt) and Cx43mentioning
confidence: 99%
“…Transcriptome analysis of brain and inner ear stria vascularis has also revealed that many genes are altered after loss of individual connexins, implying that the protein may tightly and coordinately control the expression of multiple genes (90, 95,230,231,363,581), which contribute to a variety of branches of the mammalian transcriptome, and possibly of the cognate proteins. The apparently selective and coordinated effect of different connexins on the genome, with the expression of a number of genes being up-or downregulated in parallel, also provides for an efficient amplification of the connexin effect, which could explain why the functional loss of a single connexin can induce dramatic phenotypes, in spite of the persistence of junctional coupling provided by other connexin isoforms (69,110,175,263).…”
Section: E Other Connexin Signaling Modalitiesmentioning
confidence: 99%